Di che cosa parliamo quando parliamo di Federico Caffè - De Bonis, Riccardo (Argomenti, 2017)
This article is a testimonial to Federico Caffè’s scientific contribution thirty years after his disappearance. It focuses on his dissemination of foreign economic theory, on his intellectual development and methodology, on his consideration of Italian economists, on the concept of economic policy and on the main lessons that Caffè left us.